The Effect of Personal Selling of Iconnet Products on the Buying Interest of Housing Residents in Medan City - Maria Bona Putri S; Ratih Hasanah Sudrajat (Jurnal Indonesia Sosial Teknologi, 2025)
Technology has influenced humans in their daily lives. The improvement of technological developments is able to affect aspects of life that cannot be separated from the use of the internet. It is seen in the last 5 years that the use of technology in Indonesia has grown rapidly, marked by the emergence of many internet service providers. The increase in household internet users is one of the phenomena that can be used by ICON+ to be able to attract new users. This target market will try to find alternative internet providers that can meet the needs of the internet in households at affordable prices. This study aims to measure the influence of personal selling carried out by ICON+ sales on the buying interest of people in Medan housing. This study is a quantitative research with a simple linear regression method from a total of 350 respondents. The results of this study stated that personal selling had an effect on the buying interest of residents in Medan city housing with the influence of the independent variable on the bound variable of 52.2% while the remaining 47.8% was influenced by other factors outside this study.